2007
DOI: 10.1002/jcp.21254
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization and cloning of amino acid transporter B0,+ (ATB0,+) in primary cultured rat pneumocytes

Abstract: Cationic amino acid transport in primary cultured rat pneumocytes exhibiting characteristics of alveolar epithelial type I-like cells are described. Asymmetry and activator ion dependency of (3)H-L-arginine uptake were characterized from the apical or basolateral fluid of pneumocytes grown on permeable support. Substrate specificity of transport was evaluated as a function of (3)H-L-arginine uptake inhibition in the presence of other amino acids. Transepithelial transport studies estimated (3)H-L-arginine flux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…With respect to amino acid selectivity, we found that amino acids with hydrophobic side chain, such as Trp, Leu, Met, Phe, and Ala generally interact with SLC6A14 with the highest apparent affinities, whereas glycine and positively charged amino acids generate the largest transport current at saturating substrate concentrations. These results on substrate selectivity are in agreement with previous reports ( Sloan and Mager, 1999 ; Ugawa et al, 2001 ; Umapathy et al, 2004 ; Karunakaran et al, 2008 ) and highlight the broad recognition range of amino acid substrates for the SLC6A14 family member ( Uchiyama et al, 2008 ).…”
Section: Discussionsupporting
confidence: 93%
“…With respect to amino acid selectivity, we found that amino acids with hydrophobic side chain, such as Trp, Leu, Met, Phe, and Ala generally interact with SLC6A14 with the highest apparent affinities, whereas glycine and positively charged amino acids generate the largest transport current at saturating substrate concentrations. These results on substrate selectivity are in agreement with previous reports ( Sloan and Mager, 1999 ; Ugawa et al, 2001 ; Umapathy et al, 2004 ; Karunakaran et al, 2008 ) and highlight the broad recognition range of amino acid substrates for the SLC6A14 family member ( Uchiyama et al, 2008 ).…”
Section: Discussionsupporting
confidence: 93%
“…In the lung, ATB 0,+ plays a similar scavenging role on the apical side of the airway epithelium ( Sloan and Mager, 1999 ; Sloan et al, 2003 ; Uchiyama et al, 2008 ; Paola et al, 2017 ), thus depleting essential nutrients and limiting bacteria growth in the thin and sterile airway surface layer (ASL) ( Mager and Sloan, 2003 ; Paola et al, 2017 ; Ruin et al, 2020 ). Short circuit currents evoked by amino acids and dependent on Na + have been recorded in cultured human bronchial epithelial cells and mouse trachea epithelium ( Galietta et al, 1998 ; Sloan et al, 2003 ; Ahmadi et al, 2019 ), although the [Na + ] and [Cl − ] in the thin ASL are not precisely known as two opposing models predict either a low salt condition (~50 mM) or near isotonic concentrations ( Boucher, 1999 ; Jayaraman et al, 2001 ; Song et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that SLC6A14 plays a primary role as an amino acid transporter in various epithelial cells and models [32,[48][49][50][51][52]. Taken together, SLC6A14 expression data in human and genetic studies suggest that SLC6A14 may have an important role in the lung and intestinal pathophysiology of CF patients (see Parts 1 and 2).…”
Section: Putative Biological Roles Of Slc6a14 In Cfmentioning
confidence: 94%